ASME 2012 6th International Conference on Energy Sustainability, Parts a and B 2012
DOI: 10.1115/es2012-91056
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Operation Test Results of a High Temperature Phase Change Storage for Parabolic Trough Power Plants With Direct Steam Generation

Abstract: For future parabolic trough plants direct steam generation in the receiver pipes is a promising option for reducing the costs of solar thermal energy [1]. These new solar thermal power plants require innovative storage concepts, where the two phase heat transfer fluid poses a major challenge [2]. For the regions where the heat transfer fluid is in a single phase (water or steam), sensible heat storage using molten salt [3] or concrete [4] as storage material can be applied. However, efficient energy storage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Based on the results of a lab module a 700 kWh th demo plant using radial aluminum fins in NaNO 3 was developed and built. The system was successfully operated in fixed and sliding pressure mode simulating its combination with a DSG solar power plant [10,11]. A further improvement was achieved due to the application of longitudinal fins that are clipped to the steel tube with a special steel clip.…”
Section: Stationary Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of a lab module a 700 kWh th demo plant using radial aluminum fins in NaNO 3 was developed and built. The system was successfully operated in fixed and sliding pressure mode simulating its combination with a DSG solar power plant [10,11]. A further improvement was achieved due to the application of longitudinal fins that are clipped to the steel tube with a special steel clip.…”
Section: Stationary Systemsmentioning
confidence: 99%
“…In sliding pressure mode the water mass flow is kept constant and the temperature difference ∆ LHTESS is increased by lowering the water pressure. Laing et al [11] have shown that the LHTESS itself can be operated in both modes, but that the sliding pressure mode is the preferred one in combination with the steam turbine.…”
Section: Part Load Operation Of Lhtess Coupled With the Steam Turbinementioning
confidence: 99%
“…The results showed the feasibility of the PCM unit for working in constant and sliding pressure modes (Laing et al, 2013). The low thermal conductivity of the PCM, which leads to slow charging and discharging rates, could be solved installing fins (Laing et al, 2012) or combining the PCM with an additive of high conductivity, such as graphite (Gil et al, 2010). In this sense, a parametric study determined the target costs of a finned PCM tank coupled to a DSG PTC power plant (Seitz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%